Direct search for charged Higgs bosons in decays of top quarks - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2002)
The direct search for charged Higgs boson in decays of top quarks was presented. The observations were recorded at the D0 detector at the Fermilab Tratron collider. Results showed that the direct search for charged Higgs bosons in top quark decay showed no evidence of signal for MH±<150 GeV.